Milnacipran effects on 24-hour ambulatory blood pressure and heart rate in fibromyalgia patients: a randomized, placebo-controlled, dose-escalation study. (April 2014) - Trugman, Joel M.; Palmer, Robert H.; Ma, Yimin
Abstract Objective: To characterize milnacipran effects on systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) in fibromyalgia patients using 24-hour ambulatory blood pressure monitoring (ABPM). Methods: This dose-escalation study included a 7-week double-blind treatment period and 2-week single-blind discontinuation period. Patients were randomized 2:1 to milnacipran (n = 210) or placebo (n = 111), with 50% of patients classified as 'hypertensive' at baseline (SBP ≥130 mmHg, DBP ≥85 mmHg, or current antihypertensive medication). Analyses were conducted at Weeks 4 and 7, after milnacipran dosages were escalated to 100 and 200 mg/day, respectively. Outcome measures included changes from baseline in mean ambulatory SBP, DBP, and heart rate for the 12-hour periods following the morning dose (post-AM dose) or evening dose (post-PM dose), and the entire 24-hour monitoring period. Primary outcome parameter was change from baseline in mean SBP for the 12-hour period post-AM dose. Safety analyses included adverse events and sitting vital sign readings taken at study visits. Results: Milnacipran increased ABPM vital signs at Week 4 (100 mg/day) and Week 7 (200 mg/day). Increases in the 12-hour period post-AM dose were similar at Weeks 4 and 7 (both visits: SBP and DBP, 4 to 5 mmHg; HR, 13 to 14 bpm). Mean increases in ambulatory vital signs were generally comparable between hypertensive and normotensive patients over 24-hour periods. Normal patterns of diurnal variation in blood pressure and heart rate were maintained in patients receiving milnacipran. Sitting vital signs were consistent with ABPM findings. Nausea was the most common adverse event observed with milnacipran. Conclusions: Fibromyalgia patients receiving milnacipran in this ABPM study had mean increases in blood pressure and heart rate that were consistent with those observed in clinical efficacy trials. Diurnal variation was preserved and changes were not greater in hypertensive patients than in non-hypertensive patients. These findings cannot necessarily be generalized to other patient populations. Clinical trial registration: This study was registered on clinicaltrials.gov (ID: NCT00618956).